Dexamethasone Does Not Inhibit Treadmill Training-Induced Angiogenesis in Myocardium: Role of MicroRNA-126 Pathway - Herrera, Naiara A. [UNESP]; Duchatsch, Francine [UNESP]; Tardelli, Lidieli P. [UNESP]; Dionísio, Thiago J.; Santos, Carlos F.; Amaral, Sandra L. [UNESP] (Wolters Kluwer, 2020)
Dexamethasone (DEX) has important anti-inflammatory activities; however, it induces hypertension and skeletal muscle microcirculation rarefaction. Nevertheless, nothing is known about DEX outcomes on cardiac microcirculation. By contrast, exercise training prevents skeletal and cardiac microvessel loss because of microRNA expression and a better balance between their related angiogenic and apoptotic proteins in spontaneously hypertensive rats. The purpose of this study was to investigate whether DEX and/or exercise training could induce microRNA alterations leading to cardiac angiogenesis or microvascular rarefaction. Animals performed 8 weeks of exercise training and were treated with DEX (50 μg/kg per day, subcutaneously) for 14 days. Cardiovascular parameters were measured, and the left ventricle muscle was collected for analyses. DEX treatment increased arterial pressure and did not cause cardiac microcirculation rarefaction. Treadmill training prevented the DEX-induced increase in arterial pressure. In addition, training, regardless of DEX treatment, increased microRNA-126 expression, phospho-protein kinase B/protein kinase B, and endothelial nitric oxide synthase levels associated with cardiac angiogenesis. In conclusion, this study suggests, for the first time, that treadmill training induces myocardial angiogenesis because of angiogenic pathway improvement associated with an increase in microRNA-126. Furthermore, DEX, per se, did not cause capillary density alterations and did not attenuate cardiac angiogenesis induced by training.